Effect of C1 Single‐door Laminoplasty on Symptomatic Atlas Canal Stenosis. Issue 10 (26th August 2022) - Chen, Linwei; Zhu, Xiuliang; He, Bin; Chen, Qixin; Li, Fangcai
Abstract : Objective: To verify the effect of single‐door laminoplasty combined with atlantoaxial fusion in the treatment of symptomatic atlas canal stenosis. Methods: This is a single‐center retrospective analysis. From February 2014 to January 2019, 16 patients (five were females) with an average age of 63.4 years (56–71 years) were enrolled in this study. Patients with compressive cervical myelopathy with CT scan showed an inner sagittal diameter (ISD) of C1 less than 29 mm or C1 canal space available for cord (SAC) of <12 mm were included, while isolated C1 stenosis without myelopathy or isolated C1 stenosis without atlantoaxial subluxation were excluded in this study. All patients underwent continuous heavy‐weight skull traction, atlas single‐door laminoplasty and atlantoaxial fusion. The differences in the pre‐ and post‐operative inner sagittal diameter, space available for cord, atlas‐dens interval (ADI) and compression of the spinal cord were analyzed by using CT and MRI. Functional evaluation was performed by using the Japanese Orthopaedic Association scoring system and the Neck Disability Index scoring system. Results: Single‐door laminoplasty provided a full decompression for the spinal cord while retaining the whole posterior arch. No complications were encountered except a superficial wound infection in one patient. At final follow‐up, The ADI was significantly reduced from 5.2 ± 1.8 mm to 1.7 ± 0.6 mm after surgery on average ( P  < 0.05). Average inner sagittal diameter of C1 was increased from 26.3 ± 2.6 mm to 34.9 ± 2.9 mm and the space available for cord was increased from 6 ± 1.7 mm to 17.8 ± 3.6 mm ( P  < 0.05). Meanwhile, the Japanese Orthopaedic Association (JOA) score of the 16 cases was improved from 11.4 ± 1.8 to 14.1 ± 1.4 on average ( P  < 0.05). The postoperative neck pain VAS score decreased significantly, from 2.6 ± 1.0 preoperatively to 1.3 ± 0.9 postoperatively ( P  < 0.05). The influence of neck pain on patient's life was improved from 17.8 ± 3.9 to 13.9 ± 3.3 after surgery ( P  < 0.05). At the last follow‐up, the healing of the hinge fracture and the fusion between atlas and axis were observed in all patients. Conclusions: Single‐door laminoplasty combined with atlantoaxial fusion not only provides enough space for decompression but also offers intact arch for bone grafting, suggesting that it might provide a more feasible method for the correction of symptomatic atlas canal stenosis. Abstract : Single‐door laminoplasty combined with atlantoaxial fusion is a safe and simple treatment for symptomatic atlas canal stenosis. Atlas hypoplasia usually developed symptomatic myelopathy due to degenerative factors, mainly atlantoaxial subluxation. Tha is why atlantoaxial fixation and fusion was recommended. C1 lamintectomy is a traditional and useful treatment for atlas hypoplasia, however, this operation may make the instability between C1‐2 worse. Single‐door laminoplasty not only provides enough space for decompression but also retains C1 arch for bone grafting. At the last follow‐up, the healing of the hinge fracture and the fusion between atlas and axis were observed in all patients.